Pathogenesis and defense gene response in Crocus sativus (saffron) against the root-lesion nematode Pratylenchus penetrans - Shakeel, Adnan (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.